Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Show that each of the series converges on their respective domains.

a) $$\sum_{n=1}^\infty \frac{1}{(1 + nx)^2}, x \in (0,\infty)$$

b)$$\sum_{n=1}^\infty e^{-nx}, x \in(0,\infty)$$

For the first one, I have said that $$\sum_{n=1}^\infty \frac{1}{(1 + nx)^2} < \sum_{n=1}^\infty \frac{1}{ n^2}$$ for all $x \in(0,\infty)$ and since $\sum_{n=1}^\infty \frac{1}{ n^2}$ converges then by the comparison test $\sum_{n=1}^\infty \frac{1}{(1 + nx)^2}$ converges for all $x>0$

For the second one, I have said that $$\sum_{n=1}^\infty e^{-nx} < \sum_{n=1}^\infty e^{-n} = \sum_{n=1}^\infty \left(\frac{1}{e}\right)^n$$ and since $\sum_{n=1}^\infty \left(\frac{1}{e}\right)^n$ converges because its a geometric series, then by the comparison test ,the series $\sum_{n=1}^\infty e^{-nx}$ converges for all $x>0$

Please tell me if this is correct or what is the correct way for these problems.

share|cite|improve this question
For the first, say it is $\lt \frac{1}{x^2}\cdot\frac{1}{n^2}$. For the second, don't throw away the $x$, you have a geometric series. – André Nicolas Apr 25 '14 at 22:41
@André Nicolas ok thanks! – user143612 Apr 25 '14 at 22:51
I dont know how to comment on a user's answer, but thanks to Alex Zorn and Nicholas Stull – user143612 Apr 25 '14 at 22:57
@AndréNicolas can I say $\sum_{n=1}^\infty \frac{1}{n^2}$ converges so $\frac{1}{x^2}\sum_{n=1}^\infty \frac{1}{n^2}$ also converges? – user143612 Apr 25 '14 at 23:07
Yes, $x$ us fixed, so $1/x^2$ is a constant. – André Nicolas Apr 25 '14 at 23:22

It's not true that:

$$\frac{1}{(1 + nx)^2} < \frac{1}{n^2}$$

You'll want to take Andre's suggestion and do:

$$\frac{1}{(1 + nx)^2} < \frac{1}{(nx)^2}$$

For the second one, it's also not true that

$$e^{-nx} < e^{-n}$$

For the second one, you don't even need to do a comparison test: The series is already a geometric series with common ratio $e^{-x}$.

share|cite|improve this answer

Hint on the first:

As Andre suggested, use instead $$\frac{1}{(1+nx)^2} \leq \frac{1}{(nx)^2}$$ and now you can write the following: $$\sum_{n=1}^\infty \frac{1}{(1+nx)^2} < \sum_{n=1}^\infty \frac{1}{(nx)^2} = \frac{1}{x^2}\sum_{n=1}^\infty \frac{1}{n^2}$$ Note you need $x > 0$ (or at least $x\neq 0$) for the term $\frac{1}{x^2}$ to be finite, and from there, what do you know about the series written in that last step?

Hint on the second one:

$$\sum_{n=1}^\infty e^{-nx} = \sum_{n=1}^\infty \left(e^{-x}\right)^n$$

Now, this is a geometric series. When do geometric series converge? (and what would this mean in terms of $x$?)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.